ANALYSIS OF PUBLIC TRUST IN BANKING SERVICES: A COMPARATIVE STUDY OF CONVENTIONAL BANKS AND SHARIA BANKS IN MAKASSAR CITY - D Talli, Abdul Safrin; Sulaiman (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study analyzes the level of public trust in banking services by comparing the perceptions of conventional bank customers and Islamic bank customers in Makassar City. The study uses a cross-sectional survey design involving 400 respondents selected through stratified purposive sampling so that the data obtained can represent community groups based on the type of bank used. The results show that, in general, both types of banks received relatively high trust scores, indicating that the people of Makassar City have a positive view of banking services. However, there are differences in the dominant factors that influence customer trust levels in each type of bank. In conventional banks, the main factors are consistent service quality and good institutional reputation. This shows that the image of professionalism, credibility, and excellent service are key to maintaining customer trust in conventional banks. Conversely, in Islamic banks, customer trust is more determined by compliance with sharia principles, followed by service quality. This means that the dimensions of religiosity and Islamic legal compliance values are crucial aspects that cannot be ignored by Islamic banks in managing their relationships with customers.